Legislação ambiental e economia do crime na BR-163 e PA-370: análise do mercado madeireiro ilegal - CARVALHO, Abner Vilhena de (Companhia Brasileira de Produção Científica, 2023)
The state of Pará is home to a significant portion of regional vegetation, and this opens the economic eye toward profitability - licit and illicit, that the forest can generate through logging. The Environmental Crimes Law was created to combat and punish environmental illicit such as illegal logging. In this sense, the general objective is to carry out the environmental economic analysis about the seizure of illegal wood from processes processed / judged and finalized under the jurisdiction of the archive of the Santarém Forum (PA), registered in the years 2006-2016. The data come from cataloging performed in the archive of the Forum of Santarém, tabulating: the year of infraction; the type of person who committed the crime; the type of charge seized - identifying the volume and the species (s); as well as the fine imposed by environmental agents and the final fine paid. From this, through statistical programs, the methodological technique of cost-benefit estimation of the illegal timber market was applied, which compared the estimated value of the load - environmental economic loss, with the fine that was paid by the offender after the final decision given by the judge. The analysis of the results was based on the specificity of Law 9.605 / 98 regarding illegal logging and, in Gary Becker's economic theory, focused on the analysis of criminal activities. In sum, it was observed in the results that the estimated value of the charge seized, in almost all cases was greater than the fine imposed, the latter can still be paid in installments, making the environmental recomposition is minimal. It is evident that if the initial penalty were applied, the offender's average profit margin would be approximately 31.74% in relation to the potential benefit, which, according to Becker's theory, would keep the illegal activity in full employment. operation. However, the results show that, on average, that profit margin of the potential crime benefit amount is approximately 67%, which makes logging illegally attractive and rewarding, as the 'potential benefit' of the activity has been quite higher than the economic costs of the penalties. Therefore, it is necessary to apply more effectively the Law on environmental crimes, as well as governance activities in relation to hiring more environmental agents to prevent, combat and seize loads that are out of illegality, as well as greater activity judiciary in judging cases.